Obtenção e caracterização do recobrimento biomimético do titânio com hidroxiapatita dopada com nitrato de prata e recoberta com filme de quitosana - Ricci, Virgilio Pereira (2017)
The titanium has excellent mechanical properties, resistance to corrosion and also has interaction with the bone, however, it is necessary a coating with a material that better perform this function, as an alternative was used hydroxyapatite, the main constituent of the bones promoting local bone regeneration. In the first days post-implant the risk of infections is very high, and the use of medications is necessary, in this way, the use of silver nitrate acting as bactericide, can decrease the indication for this drug a controlled form of release of this bactericide is adequate, so the use and study of polymer films for this purpose have been increasingly studied. Thus, in this work the coating of titanium with hydroxyapatite, doped with silver nitrate and coating with chitosan film was carried out. In this work was studied the commercially pure titanium, grade 4, without coating (Ti cp), titanium cp with biomimetic coating of hydroxyapatite (C0), titanium cp with biomimetic coating of hydroxyapatite doping of silver nitrate (C1) and titanium cp with biomimetic coating of hydroxyapatite doping of silver nitrate and coating with chitosan film (C2). The coatings with hydroxyapatite, doping with silver nitrate and the coating with chitosan film were characterized by SEM/EDS techniques, where the coatings presented the characteristic morphology in the XRD, the characteristic peaks of phase , hydroxyapatite and chitosan and with the FTIR the peaks referring to the compounds present in hydroxyapatite and chitosan. The bioactivity test presented the formation and increase of the hydroxyapatite layer in all conditions studied. In the corrosion tests, samples coated with chitosan film showed better resistance to corrosion. In the microbiological tests the silver nitrate was efficient and the chitosan film was efficient in the slow release of the silver.